2013
DOI: 10.1080/14786419.2012.704371
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol distribution in plant organs of tomato introgression lines

Abstract: The content of total polyphenols, chlorogenic, caffeic (CaA) and ferulic acids, and rutin, was investigated in plant organs of three introgression lines (IL7-3, IL10-1 and IL12-4) of Solanum pennellii in Solanum lycopersicum cv M82 and compared with that of cropped parental. Such study aims to evidence factors associated to the introgressions that can affect polyphenol distribution in plant. Among genotypes few differences in polyphenols were recorded on fresh weight basis. IL7-3 showed higher total polyphenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
4
12
0
Order By: Relevance
“…In some cases, the TPC in cherry varieties (ranging from 209 to 350 mg/100 g DW) were higher and in others similar to those reported in common tomatoes (ranging from 210 to 286 mg/100 g DW). These data agree well with those of other authors, for example Vinha et al (2014) (Vinha, Alves, Barreira, Castro, & Costa, 2014), who studied four tomato cultivars and reported TPC values between 54 to 67 mg gallic acid equivalent (GAE)/100 g On the other hand, TPC in common varieties in this study were higher compared with those found in others, which reported variations of concentration from 18 to 31 mg GAE/100 g FW (Gahler, Otto, & Bphm, 2003) or from 26 to 42 mg/100 g FW (Minutolo, Amalfitano, Evidente, Frusciante, & Errico, 2013). This may be due, at least in part, to the fact that in this study acidified methanol was used and this favors the extraction of phenolics according to the findings of some authors (Ju & Howard, 2003;Arranz, 2010).…”
Section: Total Phenolic Contentsupporting
confidence: 92%
See 4 more Smart Citations
“…In some cases, the TPC in cherry varieties (ranging from 209 to 350 mg/100 g DW) were higher and in others similar to those reported in common tomatoes (ranging from 210 to 286 mg/100 g DW). These data agree well with those of other authors, for example Vinha et al (2014) (Vinha, Alves, Barreira, Castro, & Costa, 2014), who studied four tomato cultivars and reported TPC values between 54 to 67 mg gallic acid equivalent (GAE)/100 g On the other hand, TPC in common varieties in this study were higher compared with those found in others, which reported variations of concentration from 18 to 31 mg GAE/100 g FW (Gahler, Otto, & Bphm, 2003) or from 26 to 42 mg/100 g FW (Minutolo, Amalfitano, Evidente, Frusciante, & Errico, 2013). This may be due, at least in part, to the fact that in this study acidified methanol was used and this favors the extraction of phenolics according to the findings of some authors (Ju & Howard, 2003;Arranz, 2010).…”
Section: Total Phenolic Contentsupporting
confidence: 92%
“…For example Pernice et al (2010) studied two tomato cherry varieties in normal, reduced and lack of irrigation and concluded that the varieties had higher contents of phenolics in reduced irrigation, while a non consistent behaviour was observed for the non irrigated samples (Pernice R. , et al, 2010); this behavior was also noticed in other studies (Sánchez-Rodríguez R. , Leyva, Constán-Aguilar, Romero, & Ruiz, 2012; Sánchez-Rodríguez, Ruiz, Ferreres, & Moreno, 2012). Again, the data demonstrate that the genotype has an important effect on the levels of the compounds (Minutolo, Amalfitano, Evidente, Frusciante, & Errico, 2013).…”
Section: Total Phenolic Contentmentioning
confidence: 77%
See 3 more Smart Citations